Vortex beams enhance IRS-aided low-rank channel transmission: principle and prototype - Zhao, Yufei (2023)
The Intelligent Reflection Surface (IRS) is a crucial technology for the development of next-generation wireless mobile networks. However, its deployment is usually limited to Line-of-Sight (LoS) transmission paths of Base Stations (BSs) due to path-loss and beamforming restrictions. LoS wireless channels are known to have low-rank characteristics, which significantly reduce the capacity of IRS-assisted communication links. To overcome this issue, we propose a new IRS transmission scheme using vortex beams. These beams have low correlation properties between different modes, thus improving the channel capacity for served users. In this paper, we detail the channel capacity comparison of IRS systems using vortex beams and conventional plane waves. Additionally, a 2-bit phase quantized IRS prototype is designed and tested through full-wave Electro-Magnetic (EM) simulations and actual transmission experiments, allowing for the conversion of mode 1 vortex beams and plane waves at a pre-determined reflection angle (e.g., ${30^° }$). Our simulation results and prototype tests show that this design is effective in manipulating reflected vortex beams and plane waves in 3D space, meeting the demands of future intelligent wireless communications.